2020
DOI: 10.1021/acs.jced.9b00902
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Thermodynamic Properties of Amino Acids in Aqueous Imidazolium-Based Ionic Liquid

Abstract: Molecular interactions of amino acids with ionic liquids are significant to study the molecular stability and physicochemical properties of amino acids. Mixtures of amino acids l-leucine and N-acetyl-l-leucine + (0.005, 0.010, 0.030, and 0.050 mol·kg–1) aqueous solution of ionic liquid (1-butyl-3-methylimidazolium chloride) at temperature T = (288.15, 298.15, 308.15, and 318.15 K) have been studied by density and speeds of sound measurements. Volumetric properties have been obtained by utilizing data of densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…Figure 7 illustrates that experimental values are consistent with those found in the literature. The speed of sound values for (water + N-acetyl L-leucine) solutions also compete with those from the literature 54,55 data and are graphically represented in Figure 8. It has been found that some literature values show deviations from experimental data at higher concentrations.…”
Section: Partial Molar Volume Of Transfersupporting
confidence: 65%
See 2 more Smart Citations
“…Figure 7 illustrates that experimental values are consistent with those found in the literature. The speed of sound values for (water + N-acetyl L-leucine) solutions also compete with those from the literature 54,55 data and are graphically represented in Figure 8. It has been found that some literature values show deviations from experimental data at higher concentrations.…”
Section: Partial Molar Volume Of Transfersupporting
confidence: 65%
“…Figure shows a graphical representation of the experimental density data for N -acetyl l -glycine compared to the literature data. Figure demonstrates that recorded densities for the ( N -acetyl l -glycine + water) binary mixture follow a similar trend as the literature densities, that is, there is a decrease in density value as temperature increases. Experimental density data for N -acetyl l -leucine were compared with literature data, , and graphically presented in Figure . From Figure it is observed that there is some deviation from the literature data at higher concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The empirically measured values of densities of both AAs ( l -valine and l -leucine) in the aqueous solution of IL are listed in Tables S2–S4. Furthermore, the density values acquired for AAs in aqueous solutions were compared with those found in the literature and are depicted in Figure S5. The analysis indicates that the experimentally measured density values align well with the literature values for the AA solution in water, as reported in refs and .…”
Section: Resultsmentioning
confidence: 99%